Book Recommendation System Based on Combine Features of Content Based Filtering, Collaborative Filtering and Association Rule Mining - Fatarphekar, Ashish; Nashikka, Tejas; Patil, Vivek; Naik, Gayatri (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2015)
Recommendation systems are widely used to recommend products to the end users that are most appropriate. Online book selling websites now-a-days are competing with each other by many means. Recommendation system is one of the stronger tools to increase profit and retaining buyer. The book recommendation system must recommend books that are of buyer’s interest. This paper presents book recommendation system based on combined features of content filtering, collaborative filtering and association rule mining.